Must deacidification with an induced flocculant yeast strain of Schizosaccharomyces pombe - Sousa, Maria João (1993)
The use of flocculant cells of the yeast strain SchizosaFcharomyces pombe for the deacidification of grape musts in continuous culture was developed. An external loop reactor was used to induce flocculation. The flocs obtained were stable in the pH range 3.0-6.0 and in the presence of several sugars. Some inhibition was observed for high (above 6.0) and low (below 3.0) pH values. Once induced, flocculation could no longer be completely inhibited. Vinho Verde, a typical Portuguese wine, has a relatively low ethanol content and a high acid concentration. The external loop reactor loaded with the flocculant cells was used to deacidify a synthetic medium with sugar and malic acid concentrations similar to the ones found in Vinho Verde grape must. A desirable malic acid decrease with moderate glucose consumption was obtained at a dilution rate of 0.7 h-1. Improved results were obtained when the synthetic medium was replaced by Vinho Verde grape must.